Case Report: Reiterating the importance of tissue biopsy in the diagnosis of tuberculosis: lessons from a case of pediatric pulmonary tuberculosis complicated by Hodgkin's lymphoma - Luo, Yonghan; Yang, Xiaotao; Zhou, Jun; Pu, Shuangqiong; Wang, Yanchun (Frontiers in Pediatrics, 2024)
The clinical symptoms of tuberculosis infection in children are not typical and need to be distinguished from many diseases, and the tumor is one of them. we present a case of cervical lymphadenopathy in a child with positive purified protein derivative (PPD) and Interferon-Gamma Release Assay results, ultimately diagnosed with Hodgkin's lymphoma via cervical lymph node biopsy. We learned some lessons from the case: First, Pathological biopsy remains the "gold standard" for diagnosing tuberculosis. Second, there are limitations of sampling in lump fine needle aspiration biopsy, surgical methods for lymph node are preferred to obtain larger tissues and improve tuberculosis detection sensitivity.